In-line Pullout Strength of 2 Acetabular Fixation Methods for Ligamentum Teres Reconstruction of the Hip: A Cadaveric Study. Issue 12 (2nd December 2021) - Lall, Ajay C.; Ankem, Hari K.; Ryan, Michael K.; Beason, David P.; Diulus, Samantha C.; Roach, Ryan P.; Rosinsky, Philip J.; Maldonado, David R.; Emblom, Benton A.; Domb, Benjamin G.
Background: Ligamentum teres (LT) reconstruction is an appropriate alternative in select cases of LT full-thickness tears, resulting in hip micro- or macroinstability. Graft fixation at the acetabular fossa is critical to achieving the best functional results. Purpose: The purpose of this study is to compare the pullout strength of 2 graft fixation methods used for LT reconstruction of the hip. Study Design: Controlled laboratory study. Methods: In 7 cadaveric specimens, the acetabular socket was prepared after the native LT was transected and the femoral head was removed. Seven separate tibialis anterior grafts were then prepared by suturing a running-locking No. 2 suture on each tail of the graft. Three specimens had fixation of the graft to the acetabulum using an adjustable cortical suspension suture button; the remaining 4 were fixed to the acetabulum using a knotless suture anchor. Specimens were then mounted onto a custom jig within a mechanical test frame to allow for the in-line pull of the graft fixation construct. After a preload of 5 N, each specimen was loaded to failure at 0.5 mm/s. Stiffness and load to failure were measured for each specimen construct. Results: Suture button fixation had a higher mean load to failure when compared with the knotless anchor fixation method (mean ± SD, 438.1 ± 114.3 vs 195.9 ± 50.0 N; P = .01). There was no significant difference in mean stiffness between the methods of fixation (24.5 ± 1.4 vs 26.5 ± 5.8 N/mm; P = .6). Conclusion: In this cadaveric study, the suture button fixation demonstrated greater load to failure than the knotless anchor fixation. Clinical Relevance: Results of this study can guide surgical decision making when selecting an acetabular fixation method for LT reconstruction.